Development of a solid‐phase microextraction fiber by the chemical binding of graphene oxide on a silver‐coated stainless‐steel wire with an ionic liquid as the crosslinking agent. Issue 24 (25th November 2014) - Sun, Min; Feng, Juanjuan; Bu, Yanan; Duan, Huimin; Wang, Xiaojiao; Luo, Chuannan
<x xml:space="preserve">Abstract</x> Graphene oxide was bonded onto a silver‐coated stainless‐steel wire using an ionic liquid as the crosslinking agent by a layer‐by‐layer strategy. The novel solid‐phase microextraction fiber was characterized by scanning electron microscopy, energy‐dispersive X‐ray spectroscopy and Raman microscopy. A multilayer graphene oxide layer was closely coated onto the supporting substrate. The thickness of the coating was about 4 μm. Coupled with gas chromatography, the fiber was evaluated using five polycyclic aromatic hydrocarbons (fluorene, anthracene, fluoranthene, 1, 2‐benzophenanthrene, and benzo(a)pyrene) as model analytes in direct‐immersion mode. The main conditions (extraction time, extraction temperature, ionic strength, and desorption time) were optimized by a factor‐by‐factor optimization. The as‐established method exhibited a wide linearity range (0.5–200 μg/L) and low limits of determination (0.05–0.10 μg/L). It was applied to analyze environmental water samples of rain and river water. Three kinds of the model analytes were quantified and the recoveries of samples spiked at 10 μg/L were in the range of 92.3–120 and 93.8–115%, respectively. The obtained results indicated the fiber was efficient for solid‐phase microextraction analysis.